2006
DOI: 10.1002/anie.200502620
|View full text |Cite
|
Sign up to set email alerts
|

Virus‐Engineered Colloidal Particles—A Surface Display System

Abstract: Colloidal particles have become valuable tools in biotechnology and medicine. Even a small sample provides a huge surface which can be engineered in many ways. One of the most versatile ways to engineer the surface of colloidal particles is to coat them with a polyelectrolyte multilayer by means of the layer-by-layer (lbl) technology. [1] Multifunctional composite colloidal devices can be fabricated in this way with nanometer precision in a radial direction. Since most of the important biomolecules-nucleic aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 30 publications
0
23
0
Order By: Relevance
“…This strategy was applied to ensure co‐delivery of both entities to the same cell. So far, lipid layers were deposited on LbL capsules for various purposes, for example to modulate the LbL shell permeability for slow release of encapsulated substances,25 to coat them with viral lipids for bead‐based multiplex assays 26, 27. The potential of lipid‐coated microcapsules for antigen delivery has not been investigated yet.…”
Section: Discussionmentioning
confidence: 99%
“…This strategy was applied to ensure co‐delivery of both entities to the same cell. So far, lipid layers were deposited on LbL capsules for various purposes, for example to modulate the LbL shell permeability for slow release of encapsulated substances,25 to coat them with viral lipids for bead‐based multiplex assays 26, 27. The potential of lipid‐coated microcapsules for antigen delivery has not been investigated yet.…”
Section: Discussionmentioning
confidence: 99%
“…VERO cells showed an enhanced uptake of virus-coated PMLCs compared to lipid-coated PMLCs without virus particles. [158][159][160][161] Such virus-functionalized particles may find applications in diagnostics, vaccination, and gene delivery. For example, Toellner et al described a bead assay based on virus-functionalized PMLCs for the simultaneous detection of viral antibodies in serum.…”
Section: Reviewsmentioning
confidence: 99%
“…Recently, bioactive adenoviral vectors embedded in multilayered polyelectrolyte films on a flat surface were shown to efficiently transfect different cell lines. [62] Fischlechner et al also suggested virus coating of LbLcoated colloids [63,64] and introduced these materials for use in multiplex suspension arrays to detect virus specific antibodies. [65] Hobson et al proposed using the extremely tight interaction between streptavidin and biotin to immobilize adenoviral vectors on the surface of wells and microparticles.…”
Section: Transduction Of the Cells On The Microcarriers By Adenoviralmentioning
confidence: 99%